Comparative Study of CURB-65, Expanded CURB- 65, PSI and SMART-COP Scoring in the Severity Assessment of Community Acquired Pneumonia - Masuduzzaman, SM; Islam, Md Sayedul; Anam, Md Khairul; Hossain, SK Shahinur; Yeasmin, Dilruba; Hossain, Muhammad Shkhawaath; Hossain, Md Delwar; Kar, Sanjoy Kumar (Chest & Heart Journal, 2021)
Background and objective: Community Acquired Pneumonia is a very common respiratory tract infection in our country. Due to overcrowding and air pollution, the number of patients and hospitalization are increasing day by day. The assessment of disease severity and site of care decisions are very important for patients’ safety and optimal use of resources. Late admission in the hospital or intensive care unit (ICU) leads to increased rate of mortality in CAP. Till now, several severity assessment scores are adopted throughout the world, but there is no study in our country regarding appropriate scoring for our population. So, this study aimed to identify the best scoring system from CURB-65, Expanded CURB-65, PSI and SMART-COP in the severity assessment of community acquired pneumonia. Patients and Methods: This study was done in the Department of Respiratory Medicine, National Institute of Diseases of the Chest & Hospital (NIDCH), Mohakhali, Dhaka over a period of two year from July, 2018 to June 2020. It was a cross sectional analytical study. Patients admitted in this hospital with signs/symptoms of pneumonia like cough, haemoptysis, shortness of breath, chest pain, crackles on chest auscultation and consolidation in CXR were enrolled as the study population. Total 54 patients were found fulfilling the inclusion criteria. The outcome of the patients were recorded in terms of hospital stay, need for ICU admission and in hospital mortalily. Result: At the end of the study, it was found that the median length of hospital stay was 8 days, intensive care unit (ICU) admission rate of CAP patients was 12(22.2%), mortality of CAP patients was 3(5.6%). Expanded CURB-65 score (5-8), SMART-COP score (5-9) and PSI class (V) were associated with more frequent ICU admission (66.7%) (n=8) in this study. Sensitivity and specificity in predicting ICU admission were 75.0% and 85.7% for CURB- 65 (Ç2=17.14, df=1, p<0.001), 75.0% and 88.1% for Expanded CURB-65 (Ç2=19.34, df=1, p<0.001), 83.3% and 81.0% for SMART-COP (Ç2=17.35, df=1, p<0.001), 91.7% and 85.7% for PSI (Ç2=25.90, df=1, p<0.001) respectively. Sensitivity for predicting mortality was 100.0% in all scoring system and specificity of CURB-65 was 76.5% (Ç2=8.25, df=1, p- .004), 78.4% for Expanded CURB-65 (Ç2=9.07, df=1, p=.003), 70.6% for SMART-COP (Ç2=6.35, df=1, p=.012) and 72.5% for PSI (Ç2=6.91, df=1, p=.009). Among the four scoring, Expanded CURB-65 had best specificity both in predicting ICU admission and mortality of CAP. Conclusion: The present study concluded that Expanded CURB-65 score is simple, objective and more accurate scoring system for evaluation of CAP severity and can improve the efficiency of predicting ICU admission and mortality better than CURB-65, PSI and SMART-COP scores. Chest Heart J. 2020; 44(2) : 73-81